Understanding process atmosphere interactions in Electron Beam Powder Bed Fusion (EB-PBF) additive manufacturing - Burgman, Oskar; Lundberg, Christian (My University, 2021)
The composition of the process atmosphere and its effect on the Ti-6Al-4V powder during Electron Beam Melting with an Arcam Q20plus was studied. Oxygen concentration and water vapour content were monitored in-situ in the build chamber and in the gas exiting the chamber, using lambda sensors and a dew point meter. Composition changes were analysed in the process atmosphere using mass spectrometry and in Ti-6Al-4V powder, using X-ray photoelectron spectroscopy, Inert Gas Fusion Analysis, and Scanning Electron Microscopy. Results show that the low supply of oxygen introduced from the process atmosphere result in the moderate increase in oxygen content, measured in the powder. The powder used had a high initial oxygen concentration, which could also explain the low oxygen pick-up seen in the study. A limited increase in oxide layer thickness can be observed on the studied powder, in agreement with the moderate increase in general oxygen content. The powder morphology and overall visual appearance studied in scanning electron microscopy also remained unchanged. The study also shows that residual air and water are notable constituents of the process atmosphere as the process starts. These constituents are gradually replaced by helium during the first few hours of the manufacturing process, while preheating occurs, where the oxygen content stabilises to a partial pressure below 0.1 ppm in the process. This is within the limit of oxygen contained in the helium. No significant variations in the oxygen content in the atmosphere between builds was registered. The gas flow exiting the Q20plus proved to be insufficient for the extractive lambda sensor and the dew point meter, rendering them unusable for this specific process. The mass spectrometry results potentially indicate minor air leaks into the vacuum chamber, as the relative amounts of nitrogen remain stable.
Keywords: additive manufacturing; electron beam melting (EBM); Ti-6Al-4V; powder; vacuum; oxygen uptake; mass-spectrometry; process gas monitoring